STILISTIKA MORFOLOGI DALAM AYAT-AYAT PENCIPTAAN MANUSIA - Nur Amalia Sholihah (AL ITQAN: Jurnal Studi Al-Qur'an, 2017)
This paper examines the language style contained in the verses of the human creation process. The problems studied include the stylistics of the Qur'an from the aspect of morphology and its implications for the meaning contained therein. The choice of words and the structure of the sentence form in this discussion looks unique, because they have different editors in each mention. This research is part of library research. The steps taken in this research are: a) Collecting verses about the human creation process; (b) identifying the verse of the human creation process by considering two things, the first, that the words have a set of morphological meanings. The second, that these morphological meanings are presented through various constructions; (c) listing the results of identification; (d) analyzing the relationship between the construction of the verses of the human creation process with each other, both in terms of conformity and contradiction; (e) describing the analysis results and concluding. The results of this study indicate that the morphological aspects contained in the verse in the process of human creation show the miraculous side of the Qur'an. The difference in the editorial of the al-Qur`an does not lead to deviations from the meaning to be conveyed. In fact, this has the effect of meaning which explains and strengthens one another. Keywords: Stylistics, Morphology, I'jaz al-Qur'an, Implications. Abstrak Tulisan ini mengkaji tentang gaya bahasa yang terdapat dalam ayat-ayat proses penciptaan manusia. Masalah yang dikaji mencakup stilistika al-Qur`an dari aspek morfologi dan implikasinya terhadap makna yang terkandung di dalamnya. Pilihan kata dan struktur bentuk kalimat pada pembahasan ini terlihat unik, karena mempunyai perbedaan redaksi dalam setiap penyebutannya. Penelitian ini bagian dari penelitian kepustakaan (library research). Langkah-langkah yang dilakukan dalam penelitian ini adalah: (a) Mengumpulkan ayat-ayat tentang proses penciptaan manusia. (b) Mengidentifikasi ayat proses penciptaan manusia dengan mempertimbangkan dua hal, yaitu pertama, bahwa kata-kata itu memiliki sekumpulan makna morfologis. Kedua, bahwa makna-makna morfologis tersebut disajikan melalui konstruksi yang beragam. (c) Membuat daftar hasil identifikasi. (d) Menganalisa hubungan konstruksi ayat-ayat proses penciptaan manusia satu sama lain, baik hubungan persesuaian maupun pertentangan. (e) Mendeskripsikan hasil analisa dan menyimpulkan. Hasil penelitian ini menunjukkan bahwa aspek morfologi yang terdapat dalam ayat proses penciptaan manusia menunjukkan sisi kemu’jizatan al-Qur`an. Perbedaan redaksi al-Qur`an tidak membawa penyimpangan terhadap makna yang ingin disampaikan. Justru hal ini membawa pengaruh pemaknaan yang saling menjelaskan dan menguatkan antara satu dengan lainnya. Kata Kunci: Stilistika, Morfologi, I’jaz al-Qur’an, Implikasi